2016
DOI: 10.1038/cmi.2015.106
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1-induced ERK/GSK-3β/Snail signaling facilitates the epithelial–mesenchymal transition and promotes the migration of MCF-7 human breast carcinoma cells

Abstract: Monocyte chemoattractant protein-1 (MCP-1) is a chemotactic cytokine that can bind to its receptor cysteine-cysteine chemokine receptor 2 (CCR2) and plays an important role in breast cancer cell metastasis. However, the molecular mechanisms underlying MCP-1-induced alterations in cellular functions during tumor progression are poorly understood. Here, we showed that MCP-1 stimulated the epithelial-mesenchymal transition (EMT) and induced the tumorigenesis of breast cancer cells by downregulating E-cadherin, up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 54 publications
2
59
0
Order By: Relevance
“…Furthermore, we addressed the underlying mechanism by which the expression of snail was down-regulated in the radixin knockdown cells. There are at least three signaling pathways contributing to the regulation of snail and E-cadherin, including ERK pathway, Akt pathway and NF-κB pathway: The inhibition of ERK by U0126 attenuated the MCP-1-induced phosphorylation of GSK-3β and decreased the expression of snail, leading to the restoration of E-cadherin in MCF-7 cells [30]; Activation of Akt led to a significant reduction in E-cadherin expression following nuclear accumulation of snail, suggesting a role for the Akt signaling pathway in the transient repression of E-cadherin in prostate cancer [31]; Treatment with Celastrus orbiculatus induced nuclear exclusion of NF-κB, which in turn led to down-regulation of snail in SGC-7901 cells. As a result, the expression of E-cadherin was up-regulated and metastatic potential was suppressed [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we addressed the underlying mechanism by which the expression of snail was down-regulated in the radixin knockdown cells. There are at least three signaling pathways contributing to the regulation of snail and E-cadherin, including ERK pathway, Akt pathway and NF-κB pathway: The inhibition of ERK by U0126 attenuated the MCP-1-induced phosphorylation of GSK-3β and decreased the expression of snail, leading to the restoration of E-cadherin in MCF-7 cells [30]; Activation of Akt led to a significant reduction in E-cadherin expression following nuclear accumulation of snail, suggesting a role for the Akt signaling pathway in the transient repression of E-cadherin in prostate cancer [31]; Treatment with Celastrus orbiculatus induced nuclear exclusion of NF-κB, which in turn led to down-regulation of snail in SGC-7901 cells. As a result, the expression of E-cadherin was up-regulated and metastatic potential was suppressed [32].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is generally accepted that the suppression of E-cadherin expression mainly occurs at transcriptional level, and several transcription factors that repress its transcription have been recognized, including zinc finger factors snail, slug, zeb1 and zeb2, basic helixloop-helix factors E47 and twist [27][28][29]. Furthermore, increasing evidence revealed that these transcription factors could be regulated via several signaling cascades, including ERK pathway, Akt pathway and NF-κB pathway [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Further, EMT confers on cancer cells mesenchymal traits and an ability to enter the CSC state. Recent studies show that breast tumor progression and EMT are activated by ERK/GSK-3β/Snail (Li et al, 2016) and both NF-κB and β-catenin signaling (Luo et al, 2016) mediated by MCP-1 and VEGF/NPR respectively. In this context, it may speculate that ERK/GSK-3β/Snail and NF-κB and β-catenin signaling may induce MSCs to secret tumor initiating growth factors that stimulates sphere formation or growth of CSC-like cell.…”
Section: Tumor Cell Interactions With the Mesenchymementioning
confidence: 99%
“…In our vitro experiments, we further elucidated that PRKAR1A deficiency up-regulated snail expression by the activation of ERK pathway, which was critical for the initiation and progression of numerous cancers414243. ERK kinase could activate Snail to further regulate EMT4445. Collectively, through the modulation of ERK/Snail/E-cadherin signaling pathway, PRKAR1A could act as a tumor suppressor gene by inhibiting lung adenocarcinoma growth and metastasis.…”
Section: Discussionmentioning
confidence: 75%